Occupational Stress and Its Impact on Psychological Health of Private College Teachers with the Mediation Effect of Coping Strategies in Chennai City - Mohideen, Mohamed; Katta, Ashok Kumar (Journal of Neonatal Surgery, 2025)
The study sought to identify the variables influencing Chennai's private college instructors' psychological health, coping strategies, and work-related stress. The global financial crisis and the growth of globalization were ascribed by the International Labour Organization (ILO) to stress and rising demand. 250 academics who received questionnaires participated in the study, along with 220 professors from other institutions in Chennai. Only 220 were suitable for additional examination. Structural equation modelling, confirmatory factor analysis, quantitative statistics, and percentage analysis were used to examine the data. According to the study's findings, coping strategies and social support two essential psychological resources are important in lowering stress. The results advance our knowledge of how coping strategies help people cope with stress.